Pengaruh Pemberian Rendam Kaki Dengan Air Jahe Merah Hangat Terhadap Penurunan Tekanan Darah Pada Tn. S dengan Diagnosa Hipertensi Di Desa Sungai Alang Kec. Karang Intan 2 Kab. Banjar - Herawati; Lestari, Winda (Nerspedia, 2024)
Background: Hypertension can be interpreted as an increase in blood pressure from the normal range.  Objective: Provide nursing care through the intervention of giving a foot soak with warm red ginger water in hypertensive clients. Methode: The data was collected using a Gordon pattern nursing assessment sheet  Results and Discussion: The results of nursing care after 3 days with the main intervention of soaking the feet with warm red ginger water,  Conclusion: There was a decrease in blood pressure after soaking the feet with warm red ginger water for 3 days.